GENDER PATTERNS IN HOUSEHOLD HEALTH EXPENDITURE ALLOCATION IN NIGERIA (2014)
Healthcare seeking behaviour among household members often depends on the decision-making structure and headship of the household. In Nigeria, the male is assumed to be de-facto head who takes daily socio-economic household decisions that relate to financial allocations. The implication of this is a possible gender bias in the decision-making and outcomes. While gender bias has been examined within households in Nigeria generally, its incidence and influence on healthcare needs, utilisation and spending have received little or no attention. This study, therefore, analysed gender patterns in household health expenditure allocation in Nigeria through the decision-making processes preceding the expenditure. A non-cooperative bargaining theory of household was applied. It permits individuals to control his or her resources while ensuring they contribute toward the welfare of other members. A combination of the Hurdle model and Engel curve approach was used. The Hurdle model involved healthcare needs, utilization, spending decision and healthcare (conditional) expenditure. The first three stages of the model were estimated through probit technique, while the last stage was estimated through Ordinary Least Squares (OLS) technique. The Engel curve (unconditional healthcare expenditure) was also estimated using OLS. The models were estimated at both household and individual levels. They were structured to take care of life-cycle implications of gender patterns by examining effects of age in years and age groups (0-9, 10-19, 20-39, 40-59 and 60+) on healthcare decisions. Data were drawn from the 2010 Harmonised Nigeria Living Standard Survey (HNLSS) conducted by the National Bureau of Statistics (NBS). The survey covered 332,938 individuals drawn from 73,329 households in the six geo-political zones. Analyses were conducted nationally, for urban and rural households and data were analysed at p≤0.05. Significant differences in gender patterns of household health expenditure allocation were observed at both household and individual levels. Females reported a high incidence of illness (β=0.038), utilised more healthcare (β=0.038) and got more conditional health expenditure allocation (β=0.043). At the household level, female groups significantly exhibited more healthcare needs than their corresponding male groups, except in age 0-9 where males exhibited more needs. Also, a similar pro-female pattern was exhibited at utilisation and spending decision stages but different with the pattern of health expenditure. While more spending was allocated to male 0-9, and beyond age 19, the pattern was reversed as females got significant allocations more than their male counterparts at the adult life-cycle. Urban and rural households also followed the pro-female pattern. Generally, health expenditure increased at younger age, declined as individuals grew but later increased at old age. Expenditure by females increased more rapidly compared to males at old age. It was remarkable that females got more allocation than males in household health expenditure by age and location in Nigeria. Therefore, health expenditure allocation, particularly by government, should reflect this pattern and difference.